2014
DOI: 10.1186/1750-1172-9-12
|View full text |Cite
|
Sign up to set email alerts
|

The supposed tumor suppressor gene WWOX is mutated in an early lethal microcephaly syndrome with epilepsy, growth retardation and retinal degeneration

Abstract: BackgroundWWOX, encoding WW domain-containing oxidoreductase, spans FRA16D, the second most common chromosomal fragile site frequently altered in cancers. It is therefore considered a tumor suppressor gene, but its direct implication in cancerogenesis remains controversial.Methods and resultsBy whole-exome sequencing, we identified a homozygous WWOX nonsense mutation, p.Arg54*, in a girl from a consanguineous family with a severe syndrome of growth retardation, microcephaly, epileptic seizures, retinopathy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
114
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(127 citation statements)
references
References 22 publications
13
114
0
Order By: Relevance
“…Few genes are known to underlie recessive forms of IEE. WWOX has been pointed as one of them in one family study to date 20. We provide data substantially confirming this finding in five patients from four families.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Few genes are known to underlie recessive forms of IEE. WWOX has been pointed as one of them in one family study to date 20. We provide data substantially confirming this finding in five patients from four families.…”
Section: Introductionsupporting
confidence: 84%
“…The phenotype in the second family ‘closely resembled the index family’,14 which allowed validating WWOX mutations in SCAR12. In contrast, the developmental phenotype of affected individuals in the third consanguineous family was much more severe 20. Indeed, the two affected siblings never acquired any developmental milestone and died before 2 years.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Another putative tumour suppressor gene recently shown to be mutated in a neurodevelopmental syndrome is WWOX. 15 16 Again, in these studies patients homozygous for loss-of-function mutations, as well as carriers, showed no cancer predisposition.…”
Section: Discussionmentioning
confidence: 74%
“…The WWOX-associated phenotype displays a wide range of phenotypic abnormalities which might be related to the nature of mutations; point mutations (such as p.P47T, p.P47R, p.G372R) are usually associated with milder phenotypes than those associated with nonsense mutations (such as p.R54*, p.K297*, p.W335*) or partial/complete deletions (Abu-Remaileh et al 2015). Nonsense or null mutations exhibited severe phenotype including progressive microcephaly, severe early onset spasticity, infantile epileptic encephalopathy, optic atrophy, failure to thrive, and premature death or abortion (Abdel-Salam et al 2014, Ben-Salem et al 2015, Tabarki et al 2015, while missense mutations in our patients and others cause a milder phenotype with no progressive microcephaly, no spasticity or spasticity with exaggerated reflexes (Mallaret et al 2014). Interestingly, neither our patients nor others had developed tumors, however, this does not negate a cumulative lifespan risk to develop cancer.…”
Section: Discussionmentioning
confidence: 99%